A prospective comparative study of intravenous alendronate and ibandronate for the treatment of osteoporosis. Issue 6 (February 2019) - Horikawa, Akira; Miyakoshi, Naohisa; Hongo, Michio; Kasukawa, Yuji; Kodama, Hiroyuki; Shimada, Yoichi
Abstract: Rationale: Few comparative studies have evaluated the differences between intravenous alendronate (ALN) and ibandronate (IBN) in patients with osteoporosis. This study was to compare the effects of these 2 drugs on bone mineral density (BMD), bone metabolic markers, and adverse events in patients with osteoporosis. Patient concerns: Seventy-eight subjects were assigned to the ALN group and 66 to the IBN group. Diagnoses: The diagnosis of osteoporosis was based on BMD values of the femoral neck or lumbar spine less than −2.5 SD below the reference values. Interventions: This study was designed as a 52-weeks, prospective, non-randomized study involving a parallel-group comparison between intravenous ALN and intravenous IBN in elderly women with osteoporosis. Outcomes: The non-switched-IBN subgroup showed significant decrease in serum collagen type I cross-linked telopeptide (NTX) at 6 and 12 months compared with baseline, and the decrease in NTX were significantly greater in the non-switched-IBN subgroup than in the non-swithed-ALN subgroup. BMD in the lumbar spine in the non-switched-IBN subgroup showed a significant increase at 12 months and the increase in BMD were significantly larger than in the non-switched-ALN subgroup. Lessons: Intravenou IBN might result in a significantly greater increase of BMD and decrease in NTX, but it had a higher incidence of adverse drug reactions than ALN.